Antibiotic use in pre-school children and the correlation with adult educational levels in two Nordic counties: a replication of a 20-year-old study. Issue 4 (3rd April 2021) - Hansen, Matilde Bøgelund; Thorsted, Anne Bonde; Ivarsson, Stina; Tyrstrup, Mia; Hedin, Katarina; Melander, Eva; Arpi, Magnus; Jakobsen, Helle Neel; Brogaard, Emma; Jensen, Jette Nygaard
Abstract: Objective: The aim of this study was to describe the change of antibiotic prescribing in pre-school children in the municipalities of the former Copenhagen County in Denmark and Skåne County in Sweden after 20 years of antibiotic stewardship effort. Furthermore, the variation in the prescribing of antibiotics between the municipalities and the correlation between municipal adult educational level and antibiotic prescribing in pre-school children was assessed. Methods: In this ecological study, information on antibiotic prescribing in pre-school children was obtained from a central pharmacy settlement system in each Region. The antibiotic prescribing rate was expressed in defined daily doses per 1, 000 inhabitants per day (DDD/TID) and number of prescriptions/1000 inhabitants. Information on municipal adult educational levels was obtained from Statistics Denmark and Statistics Sweden. Results: The antibiotic prescribing rate during 2017 was higher in the municipalities of Copenhagen County (5.6–7.9 DDD/TID) compared to the municipalities of Skåne County (4.2–6.6 DDD/TID). In 1998 a higher rate was found in Skåne County (9.6–17.7 DDD/TID) compared to Copenhagen County (8.0–12.9 DDD/TID). A non-significant negative correlation between adult educational levels and antibiotic prescribing was observed in the municipalities of Copenhagen County ( r = −0.233, p  = .352) while the correlation was positive in the municipalities of Skåne County ( r = +0.410, p  = .018). The same correlations were observed in 1998. Conclusion: We found higher antibiotic prescribing in pre-school children in the municipalities of Copenhagen County compared to Skåne County in 2017, suggesting a possible overuse of antibiotics in Denmark. Further research should try to elucidate the reasons for the observed variation.